2013
DOI: 10.5121/ijait.2013.3102
|View full text |Cite
|
Sign up to set email alerts
|

Mobility Assisted Dynamic Routing for Mobile Wireless Sensor Networks

Abstract: Wireless Sensor Networks (WSNs) is one of the most rapidly growing research domain. This is because of the development of sensor nodes with extremely low cost and the applications of such sensor nodes are ever growing. WSNs are group of sensor nodes with a set of processors and limited memory unit. Reliable routing of packets from sensor nodes to its base station is the most important task for these networks. Also mobility of the nodes is considered to be one major criterion for WSNs. In this paper, a dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Studies have shown that moderate exercise and proper nutrition can stimulate the growth and development of children and adolescents. It can also improve cardiopulmonary function, increase endurance, reduce body fat, and increase strength and many other health benefits [13]. This article randomly selected 80 boys and 60 girls from a certain school to investigate their physical activity levels during study days and weekends.…”
Section: Physical Activitymentioning
confidence: 99%
“…Studies have shown that moderate exercise and proper nutrition can stimulate the growth and development of children and adolescents. It can also improve cardiopulmonary function, increase endurance, reduce body fat, and increase strength and many other health benefits [13]. This article randomly selected 80 boys and 60 girls from a certain school to investigate their physical activity levels during study days and weekends.…”
Section: Physical Activitymentioning
confidence: 99%
“…Wireless sensor networks are used for the collection, transmission and convergence of environmental data in smart buildings [14]. The sensor network has a tree network topology structure composed of sensor nodes, cluster head nodes and aggregation nodes to realize the transformation of sensor data flow from generation to aggregation [15][16].…”
Section: Wireless Sensor Network Architecture Designmentioning
confidence: 99%
“…As long as the source node receives the result of the optimal path, it starts to send data directly based on this result, and does not need to occupy local resources to calculate the next hop node like the traditional trust model. In addition, the optimal path selection module can not only calculate trust weights, energy weights, and risk weights, but also plan the initialization of data in the network, and specify the storage and access methods of data [15].…”
Section: Trust Model Of Wireless Sensor Networkmentioning
confidence: 99%